An actuarial model of the national health insurance program (PhilHealth) - De Leon, Yolanda Macas
Modeling is one method of measuring the performance of Social Health Care schemes, internationally, nationally or locally. This paper discusses the development of an actuarial valuation model of the social health insurance program being administered by the Philippine Health Insurance Corporation. Tha actuarial model that was developed has the main function of calculating the annual revenues and expenditure, and assessing the financial sustainability of PhilHealth based on certain actuarial assumptions over an eleven (11) year period. It is a collective and open-ended model of a health care system serving a huge population, not only with respect to the contributors, but with respect to their dependents as well.